The practical use of Kit-Build concept map on formative assessment - Jaruwat Pailai; Warunya Wunnasri; Kan Yoshida; Yusuke Hayashi; Tsukasa Hirashima (The Asia-Pacific Society for Computers in Education (APSCE), 2017)
Abstract Formative assessment can encourage an instructor to improve learning achievements in a lecture class. The goal of formative assessment in a classroom situation is monitoring learners to provide instructor's feedback for improving learner's understanding as well as instructor's expectation. A Kit-Build concept map is a digital tool for supporting a concept map strategy to represent instructor's expectation and to assess the current understanding of learners. The Kit-Build concept map is also adequate for implementing the formative assessment in a lecture class. The proposition level exact matching between the concept map of instructor and learners can generate the diagnosis results for informing the instructor about the gaps between current learner's understanding and the instructor's expectation. Accordingly, the instructor can design the feedback based on the diagnosis results for improving the understanding of learners. In this paper, we propose the arrangement of the ability of the Kit-Build concept map on formative assessment in a lecture class for creating an opportunity to assess current understanding of learners as more as possible. And we present the effectiveness of the Kit-Build concept map on the closed-end approach in elementary school through three practical uses in various lecture classes, which illustrate the contribution of the Kit-Build concept map when utilized on formative assessment in the lecture class.